Impact of Cognitive Remediation Therapy on Neurocognitive Processing in Anorexia Nervosa - Leppanen, Jenni; Adamson, James; Tchanturia, Kate (Frontiers in Psychiatry, 2018)
Background: Anorexia nervosa (AN) is characterised by severe malnutrition as well as inefficiencies in neurocognitive functioning, which are believed to contribute to the maintenance of disordered eating. The aim of this study was to examine the impact of individual cognitive remediation therapy (CRT) on neurocognition in AN. Methods: 145 adult women from an eating disorders inpatient programme took part in the present study. All participants were given individual CRT in addition to treatment as usual. Neurocognitive processes were assessed at baseline and at the end of treatment using task-based and self-report measures. The task-based measures included the Rey-Osterrieth Complex Figure test and the Brixton test, which were used to assess central coherence and set-shifting. The Detail and Flexibility Questionnaire was used to examine patients self-reported detail focus and cognitive flexibility. Results: Participants showed significant improvement in task-based measures of neurocognition following CRT. There were no significant changes in self-report measures. Conclusions: These findings suggest that CRT may be an effective intervention targeting inefficiencies in neurocognition in AN. Future studies may benefit from assessing neural changes associated with these improvements and conducting randomised controlled trials to replicate these findings.